Effects of dietary fats and carbohydrate on insulin secretion, inflammation and gastro-intestinal peptides in abdominally obese individuals: A randomized controlled trial / Chang Lin Faun - Chang, Lin Faun (2017)
Dietary recommendations promote low-fat diet but not saturated fat. This has led to increased refined carbohydrate-intake which can potentially be disadvantageous to cardiovascular-risk. To investigate the controversy surrounding present dietary guidelines, this study compared the effects of substitution of high refined carbohydrate or monounsaturated fatty acids (MUFA) for saturated fatty acids (SAFA) on insulin secretion and inflammation in abdominally-obese subjects (waist circumference: ≥80 cm for women, ≥90cm for men; 20-60 years old). Using a crossover design, randomized controlled trial in 54 subjects, we compared the effects of substitution of 7% energy as carbohydrate or MUFA for SAFA for a period of 6 weeks each where the control (SAFA) diet consisted of 15% en protein, 53% en carbohydrate and 32% en fat (12% en SAFA, 13% en MUFA). Subjects were provided three meals during weekdays and test oil for home cooking within study guidelines during weekends. Blood samples were collected at fasting, 15 and 30 min and hourly intervals thereafter till 6 hours in response to mixed meal challenge (muffin and milkshake) with SAFA or MUFA (872.5 kcal, 50 g fat, 88 g carbohydrate) or CARB (881.3 kcal, 20 g fat, 158 g carbohydrate) enrichment corresponding to the background diets. As expected, postprandial non-esterified fatty acid suppression and elevation of C-peptide, insulin and glucose secretion were the greatest with high-carbohydrate (CARB) meal. Interestingly, CARB meal attenuated postprandial insulin secretion corrected for glucose response and disposition index (P < 0.05) however the insulin sensitivity was not affected (P > 0.05). SAFA and MUFA had similar effects on all markers except for fasting glucose-dependent insulinotropic peptide (GIP) concentrations which increased after MUFA but not SAFA when compared with CARB (P < 0.05). No significant differences in fasting inflammatory and thrombogenic factors (interleukin (IL)-6, IL-1β, C-reactive protein, E-selectin, plasminogen activator inhibitor- iv 1 (PAI-1) and D-dimer) were noted between diets (P > 0.05). As indicated by incremental area under the curve during postprandial state, CARB meal was found to increase plasma IL-6 while MUFA meal elevated postprandial plasma D-dimer significantly more compared with SAFA meal (P < 0.05). Comparing the 3 meals, there were similar postprandial reductions in augmentation index and pressure. CARB diet was found to reduce HDL3 by 7.8% and increase small dense HDL (sdHDL) by 8.6% compared with SAFA diet (P < 0.05). SAFA diet increased large HDL subfractions compared with both CARB and MUFA diets by 4.9% and 6.6% (P < 0.05), respectively. In conclusion, a 6-week lower-fat/higher-carbohydrate (increased by 7% refined carbohydrate) diet may have greater adverse effect on insulin secretion corrected for glucose and disposition index compared with isocaloric higher-fat diets. In contrast, exchanging MUFA for SAFA at 7% energy had no appreciable adverse impact on insulin secretion. Overall, the evidence presented in this study suggests that the replacement of SAFA with MUFA or carbohydrates may not improve inflammatory and thrombogenic markers in abdominally obese individuals. Indeed increased high refined carbohydrate consumption adversely impacts HDL subfractions compared to high SAFA intake, hence may increase coronary heart disease risk.